An Evaluation of Health Care Waste Management in Base Hospitals of Colombo District - MASC Samarakoon; NS Gunawardena (College of Community Physicians of Sri Lanka, 2012)
Introduction Current Health Care Waste Management (HCWM) situation in Sri Lanka needs drastic improvement in order to reduce the direct/indirect adverse health impacts to health personnel and public. Objective The study aimed at evaluating HCWM of the two base hospitals in Colombo district. Methodology In a hospital based descriptive cross-sectional study in both base hospitals in the Colombo district, processes followed in relation to HCWM and availability of facilities for HCWM were assessed using an observation checklist and knowledge, attitude and practices of nursing officers (n=328) were studied using a self-administered questionnaire. Results A majority of nursing officers (97.8%) were females. Though a majority (57.9%) had >10 years working experience, only 36.9% had received a formal training in HCWM. Overall knowledge regarding HCWM was 'poor' in 59.5%. A majority of study population had favourable attitudes in implementing HCWM and 'good' practices related to HCWM (74.8%). Conclusion Many gaps were identified in both hospitals in processes followed in relation to HCWM and facilities needed for effective HCWM. HCWM in both hospitals need improvement. Processes related to HCWM need to be regularized and facilities should be provided. Knowledge gaps among nursing officers need to be bridged by educational programmes to sustain the favourable attitudes and to further improve practices. Journal of the College of Community Physicians of Sri Lanka Volume 16, No. 02, December 2011 15-20 DOI: http://dx.doi.org/10.4038/jccpsl.v16i2.4576